2010
DOI: 10.1021/nn901425r
|View full text |Cite
|
Sign up to set email alerts
|

Helical Carbon Nanotubes: Catalytic Particle Size-Dependent Growth and Magnetic Properties

Abstract: The exact knowledge of helical carbon nanotube (HCNT) growth mechanism has not yet been completely clarified, and effective synthesis of high-purity helical carbon nanotubes in high yield still remains a tremendous challenge. In this study, HCNTs were synthesized via a catalytic chemical vapor deposition method using Fe nanoparticles as catalysts. We performed systematic experiments to investigate the specific effect of catalytic particle size (CPS) on the selective growth of HCNTs, such as on the morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 51 publications
(124 reference statements)
5
73
1
Order By: Relevance
“…Similar phenomena have also been noted in previous reports. [22,31] Although HCNTs have been prepared for many years, to the best of our knowledge, their application in bioassay has not hitherto been reported. One possible reason may be their poor solubility in water.…”
Section: Resultsmentioning
confidence: 99%
“…Similar phenomena have also been noted in previous reports. [22,31] Although HCNTs have been prepared for many years, to the best of our knowledge, their application in bioassay has not hitherto been reported. One possible reason may be their poor solubility in water.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal CVD on substrate bound Fe catalyst nanoparticles was also be used to fabricate helical CNTs, though the alignment was poor compared to the co-pyrolysis method. [ 168 ] CVD of helical CNTs from fl oating catalyst was achieved by injecting a xylene-ferrocene mixture having dissolved indium isopropoxide and tin isopropoxide (sources for In and Sn respectively) in a CVD furnace. Formation of helices was explained by asymmetric growth on compound catalyst nanoparticles (Fe-In) due to different carbon precipitation rates in the segregated phases of the particle.…”
Section: Oriented Nanostructure Growthmentioning
confidence: 99%
“…al synthesized coiled CNFs with additives like tiophene and H 2 S and suggested a growth mechanism for coiled carbon fibers based on the anisotropic extrusion of carbon over a catalyst particle [18,19]. It has been shown that it is possible to synthesize HCNTs and HCNFs on Fe nano particles at temperatures below 500° C [20,21].…”
Section: Introductionmentioning
confidence: 99%